Combination of umbilical cord mesenchymal stem cells and standard immunosuppressive regimen for pediatric patients with severe aplastic anemia - Yang Lan; Fang Liu; Lixian Chang; Lipeng Liu; Yingchi Zhang; Meihui Yi; Yuli Cai; Jing Feng; Zhibo Han; Zhongchao Han; Xiaofan Zhu (BMC, 2021)
Abstract Background Defects of bone marrow mesenchymal stem cells (BM-MSCs) in proliferation and differentiation are involved in the pathophysiology of aplastic anemia (AA). Infusion of umbilical cord mesenchymal stem cells (UC-MSCs) may improve the efficacy of immunosuppressive therapy (IST) in childhood severe aplastic anemia (SAA). Methods We conducted an investigator-initiated, open-label, and prospective phase IV trial to evaluate the safety and efficacy of combination of allogenic UC-MSCs and standard IST for pediatric patients with newly diagnosed SAA. In mesenchymal stem cells (MSC) group, UC-MSCs were injected intravenously at a dose of 1 × 106/kg per week starting on the 14th day after administration of rabbit antithymocyte globulin (ATG), for a total of 3 weeks. The clinical outcomes and adverse events of patients with UC-MSCs infusion were assessed when compared with a concurrent control group in which patients received standard IST alone. Results Nine patients with a median age of 4 years were enrolled as the group with MSC, while the data of another 9 childhood SAA were analysed as the controls. Four (44%) patients in MSC group developed anaphylactic reactions which were associated with rabbit ATG. When compared with the controls, neither the improvement of blood cell counts, nor the change of T-lymphocytes after IST reached statistical significance in MSC group (both p > 0.05) and there were one (11%) patient in MSC group and two (22%) patients in the controls achieved partial response (PR) at 90 days after IST. After a median follow-up of 48 months, there was no clone evolution occurring in both groups. The 4-year estimated overall survival (OS) rate in two groups were both 88.9% ± 10.5%, while the 4-year estimated failure-free survival (FFS) rate in MSC group was lower than that in the controls (38.1% ± 17.2% vs. 66.7% ± 15.7%, p = 0.153). Conclusions Concomitant use of IST and UC-MSCs in SAA children is safe but may not necessarily improve the early response rate and long-term outcomes. This clinical trial was registered at ClinicalTrials.gov, identifier: NCT02218437 (registered October 2013).